Comparison of the effects of the prebiotics (Bio-Mos and -1,3-D-glucan) and the customised probiotics (Pseudomonas synxantha and P. aeruginosa) on the culture of juvenile western king prawns (Penaeus latisulcatus Kishinouye, 1896) - Hai, Ngo; Fotedar, Ravi (Elsevier BV, 2009)
The present study investigated the effects of dietary immunostimulants on the growth, survival and immune responses of juvenile western king prawns (Penaeus latisulcatus). The immunostimulants used were two prebiotics Bio-Mos and -1,3-D-glucan and two customised probiotics Pseudomonas synxantha and P. aeruginosa. The prawn juveniles (4.630.39 g) were fed the formulated feed (control), supplemented with Bio-Mos at 0.5%, -1,3-D-glucan at 0.2% and a combination of two probiotics (105 CFU/mL at 50:50 v/v) at 20 mL/kg for 84 days of culture. The specific growth rate (SGR), survival and food conversion ratio (FCR)were higher in the prawns fed the immunostimulants than in the control. Although no significant effects on the SGR, survival and FCR were found when the prawnswere fed either any prebiotics or probiotics, the higher survivalwas observed in the prawns fed the probiotics, while the higher SGR and lower FCR were observed in the prawns fed -1,3-D-glucan, which had the most influence in increasing the surface structure of the prawn intestines. The healthier prawns showed the higher total haemocyte count (THC), the lowest clotting time and lowest bacterial load in the haemolymph when they were fed the probiotics. Continuous supplementation with the immunostimulants to the prawns for 84 days showed considerable improvement in the growth, survival and immune response of the prawns.